Guide to Graphics Software Tools - Chen, Jim X. (Springer London : Imprint: Springer, 2009)
Current graphics software and hardware combine to allow multiple-level functionality and open up new application areas for scientists of all disciplines, and for computer scientists and engineers in particular. This thoroughly revised integrated guide explains and lists readily available graphics software tools and their applications, while also serving as a shortcut to graphics theory and programming. The second edition grounds readers in fundamental concepts and helps them use visualization, modeling, simulation, and virtual reality to complement and improve their work. Features: • Comprehensive and practical coverage of software graphics tools • Includes 6 new chapters on OpenGL Programming in Java, Curved Models, Vertex Shading, Pixel Shading and Parallel Processing, Programming in Java3D, OpenGL Shading Language, Direct3D Shader Programming [NEW] • Updated graphics software tools, with new information and format [NEW] • Additional descriptions and examples [NEW] • Provides a uniquely categorized compendium of 293 3D graphics software tools • Concise listings of platforms and pricing, applications, examples, functions, and related Web resources • Shortcuts to practical graphics principles and methods • Contains extensive appendices including the addition of basic mathematics in 3D graphics [NEW] • Extensive pointers to websites and other proven helpful sources • Combines theory and OpenGL programming with an easy-to-follow approach A concise, practical introduction to graphics theory and programming, practitioners as well as advanced students will find this accessible revised text an authoritative and useful catalogue of working software tools and methods. Professor Jim X. Chen is the Director of the Computer Graphics Laboratory at George Mason University and Editor of the Visualization column, and the Visualization Portal, for the IEEE magazine, Computing in Science and Engineering. In addition he is the author of the successful Springer book Foundations of 3D Graphics Programming: Using JOGL and Java3D, also now in its second edition. Key Topics: OpenGL Programming in Java (NEW) Curved Models (NEW) Vertex and Pixel Shading in Cg on Java Platform (NEW) Programming in Java3D (NEW) OpenGL Shading Language (GLSL) in C/C++ (NEW) Direct3D and High Level Shading Language Programming (NEW) Objects and Models Transformation and Viewing Color and Lighting Blending and Texture Mapping.